The ankyrin repeat protein Diego mediates Frizzled-dependent planar polarization. - Feiguin, F.; Hannus, M.; Mlodzik, M.; Eaton, S. (Developmental Cell, 2001)
During planar polarization of the Drosophila wing epithelium, the homophilic adhesion molecule Flamingo localizes to proximal/distal cell boundaries in response to Frizzled signaling; perturbing Frizzled signaling alters Flamingo distribution, many cell diameters distant, by a mechanism that is not well understood. This work identifies a tissue polarity gene, diego, that comprises six ankyrin repeats and colocalizes with Flamingo at proximal/distal boundaries. Diego is specifically required for polarized accumulation of Flamingo and drives ectopic clustering of Flamingo when overexpressed. Our data suggest that Frizzled acts through Diego to promote local clustering of Flamingo, and that clustering of Diego and Flamingo in one cell nonautonomously propagates to others.